THE INFLUENCE OF COUNTRY OF ORIGIN (JAPAN), BRAND IMAGE, PRICE PERCEPTION AND PERCEIVED QUALITY TOWARDS REPURCHASE INTENTION: EVIDENCE FROM UNIQLO BRAND IN INDONESIA - Felix, Nicholas; Tan, Pauline Henriette Pattyranie (Indonesian Marketing Journal, 2023)
Indonesia is one of the countries with abundant population growth, as well as Indonesia is concluded as one of the countries with the most fashion users and buyers around the world. However, according to the data of sales revenue from Uniqlo in Indonesia, customers from Indonesia only contributed a little revenue towards global sales of Fast Retailing Co. or it is also called Uniqlo. This statement contradicted the point that Indonesia as one of the most fashion consumers around the world. This research aims to determine the effect and influence of country of origin, brand image, price perception, and perceived quality on repurchase intention in Uniqlo stores in Indonesia, Jakarta. This research uses explanatory research with a quantitative approach, the object of this research is people who have at least bought Uniqlo’s product more than once. The non-probability purposive sampling method was used on 200 respondents who lived in Indonesia and had purchased products from Uniqlo at least more than once. Online questionnaires were employed as the research tool for the data. The results showed that H1 Country of origin has a significant and positive effect towards repurchase intention is rejected, H2 Brand image has a significant and positive effect towards repurchase intention is accepted, H3 Price perception has a significant and positive effect towards repurchase intention is accepted, and H4 Perceived quality has a significant and positive effect towards repurchase intention is accepted. For future research, some variables such as loyalty, satisfaction, and convenience can be added to the model to predict repurchase intention.